Kiambang Extract Effectiveness Test (Salvinia molesta D.Mitch.) as Bioherbicide in Controlling Pre-growth of Peanut Weed (Cyperus rotundus L.) - Toni Sutrisno; Hapsoh Hapsoh; Herman Herman (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Kiambang extract (Salvinia molesta D.Mitch.) is an alternative to control Teki Weed (Cyperus rotundus L.), The aim of the study was to test the effectiveness of kiambang extract as a bioherbicide and to obtain the best concentration in controlling pregrowth of puzzle weed (Cyperus rotundus L.) . The research was carried out at the Experimental Garden Nursery, Riau University, Jalan Bina Widya km 12.5, Simpang Baru Village, Tampan District and at the Natural Materials and Minerals Laboratory, Faculty of Engineering, Riau University. This research was conducted experimentally using one factor Completely Randomized Design (CRD). The treatment for the pre-growth test used 5 treatments of kiambang extract concentration, namely: 0%, 20%, 40%, 60% and 80% repeated 4 times. The data obtained were analyzed using analysis of variance (ANOVA) at the 5% level, then further tested using Duncan's Multi Range Test (DMRT) at the 5% level with SPSS 23. The results showed that kiambang extract was considered effective as a pre-emergent bioherbicide to control nut weeds. . the best concentration of kiambang extract in inhibiting the shoots of nut weed tubers was the treatment with a concentration of 80%.